DESCRIPTION OF EXPERTS OF LOGISTICS ACTIVITIES TO MANAGEMENT - Гармаш, Т. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The paper presents the concept and content of training of specialists for logistics management activities; disclosed its structure, which consists of the following components: personal and motivational, cognitive-operational, communicative-activity and criteria: motivation, communication, cognitive, activity; Indexes and appropriate levels of readiness logistics professionals to administrative activity (high, sufficient, medium, low)